2016
DOI: 10.1093/ijnp/pyw069
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 101b Is Downregulated in the Prefrontal Cortex of a Genetic Model of Depression and Targets the Glutamate Transporter SLC1A1 (EAAT3)in Vitro

Abstract: Background:MicroRNAs (miRNAs) are small regulatory molecules that cause translational repression by base pairing with target mRNAs. Cumulative evidence suggests that changes in miRNA expression may in part underlie the pathophysiology and treatment of neuropsychiatric disorders, including major depressive disorder (MDD).Methods:A miRNA expression assay that can simultaneously detect 423 rat miRNAs (miRBase v.17) was used to profile the prefrontal cortex (PFC) of a genetic rat model of MDD (the Flinders Sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Energy and glutathione metabolic pathways in the prefrontal cortex were shown to be significant biological pathways in depressive rats [ 58 ]. Many studies have indicated that changes in glutamate metabolism were associated with depression [ 59 67 ]. In a stress-induced depressive mouse model, the prefrontal cortex in depression showed a significant reduction of glutamate in the GABAergic pathway, which may contribute to depression [ 62 ].…”
Section: The Prefrontal Cortex In Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy and glutathione metabolic pathways in the prefrontal cortex were shown to be significant biological pathways in depressive rats [ 58 ]. Many studies have indicated that changes in glutamate metabolism were associated with depression [ 59 67 ]. In a stress-induced depressive mouse model, the prefrontal cortex in depression showed a significant reduction of glutamate in the GABAergic pathway, which may contribute to depression [ 62 ].…”
Section: The Prefrontal Cortex In Depressionmentioning
confidence: 99%
“…In addition, a novel miRNA (miR-101b) was found to be downregulated in depression and could decrease mRNA and protein levels of glutamate transporter SLC1A1 in the prefrontal cortex [ 59 ]. In addition, in the medial prefrontal cortices of chronic unpredictable mild stress-induced depressive mice, there was a downregulation of mRNAs encoding proteins for the GABAergic synapses, dopaminergic synapses, synaptic vesicle cycle, and neuronal growth and an upregulation of miRNAs of regulating these mRNAs [ 70 ].…”
Section: The Prefrontal Cortex In Depressionmentioning
confidence: 99%
“…Among the various miRNAs, miR-146a-5p, miR-146b-5p, miR425-3p and miR-24-3p have been suggested to play an important role in treatment response [68]. In a genetic rat model of depression, miR-101b, which targets glutamate transporter, has been found to be downregulated [69]. In astrocytoma cells, miR-101 has been shown to reverse the methylation of promoter of PR domain containing 16 (PRDM16) leading to disruption of mitochondrial function, reduced ATP synthesis and initiation of mitochondria-dependent apoptosis [70].…”
Section: Mitochondria and Epigenetics Hypothesismentioning
confidence: 99%
“…Moreover, it has been demonstrated that miRNA-124 and miRNA-181a positively regulate GLT1 ( 82 , 83 ), while miRNA-107 inhibits GLT1 expression ( 84 ). Specifically, EAAC1 rhythm is negatively controlled by miRNA-96-5p ( 71 ), miRNA-26a-5p ( 85 ) and miRNA-101b ( 86 ). This former miRNA also negatively regulates to EAAC1 protein ( 86 ).…”
Section: Circadian Regulation Of Glutamate Transportersmentioning
confidence: 99%
“…Specifically, EAAC1 rhythm is negatively controlled by miRNA-96-5p ( 71 ), miRNA-26a-5p ( 85 ) and miRNA-101b ( 86 ). This former miRNA also negatively regulates to EAAC1 protein ( 86 ). However, no evidence shows that miRNAs can target EAAT4 and EAAT5.…”
Section: Circadian Regulation Of Glutamate Transportersmentioning
confidence: 99%